Comprehensive Environmental Monitoring based on Stations of Environmental Pollutants (Air, Water and Soil) in Tehran - Mohammadreza Haghparast; Seyed Alireza Haji Seyed Mirza Hosseini; Nabiollah Mansouri; Jamal Ghodousi (Environmental Energy and Economic Research, 2020)
This research is conducted with an aim of locating the monitoring stations of environmental pollutants (air, water and soil) and monitoring management of such pollutants in Tehran. Given the nature of the research and the factors and elements investigated in this study, the research method is in the line of descriptive-analytical studies, and in terms of objective, this is an applied-developmental research. In summary, the specific and practical purposes of this research include; determining the factors, criteria and sub-criteria associated with monitoring of environmental pollutants (air, water and soil), prioritizing and ranking the criteria and sub-criteria of indicators with a specific logic, and providing a pattern for management on monitoring of environmental pollutants in Tehran. ArcGis software was applied for data analysis and providing digital and basic maps. Analytic network process (ANP) was used for weighting the indicators studied in the research and the fuzzy logic model was used for data analysis and overlapping. According to the table of verbal and numerical scales based on hourly method, a pairwise comparison was performed between air, water and soil environments based on importance and preference and the data were imported into the Super-Decision software. According to the output of this software, the air weight of 673, water weight of 226, and soil weight of 101 were obtained, respectively. As a result, this output showed us that air is ranked first, water is ranked second, and soil is ranked third, in terms of importance.  From the results and prepared (weighted) maps and also in response to the research hypotheses, it was found that some of the available stations are not properly located. Finally, the location of monitoring stations was presented in four classes of very desirable, desirable, relatively desirable, and undesirable.